Gαq activation modulates autophagy by promoting mTORC1 signaling - Cabezudo, Sofía (Nat Commun, 2021)
The mTORC1 node plays a major role in autophagy modulation. We report a role of the ubiquitous Gαq subunit, a known transducer of plasma membrane G protein-coupled receptors signaling, as a core modulator of mTORC1 and autophagy. Cells lacking Gαq/11 display higher basal autophagy, enhanced autophagy induction upon different types of nutrient stress along with a decreased mTORC1 activation status. They are also unable to reactivate mTORC1 and thus inactivate ongoing autophagy upon nutrient recovery. Conversely, stimulation of Gαq/11 promotes sustained mTORC1 pathway activation and reversion of autophagy promoted by serum or amino acids removal. Gαq is present in autophagic compartments and lysosomes and is part of the mTORC1 multi-molecular complex, contributing to its assembly and activation via its nutrient status-sensitive interaction with p62, which displays features of a Gαq effector. Gαq emerges as a central regulator of the autophagy machinery required to maintain cellular homeostasis upon nutrient fluctuations.